O96 Large inter- and intra-rater variation on diagnostic criteria for amyotrophic lateral sclerosis. Issue 9 (September 2017) - Johnsen, Birger; Pugdahl, Kirsten; Fuglsang-Frederiksen, Anders; Kollewe, Katja; Paracka, Lejla; Dengler, Reinhard; Camdessanché, Jean-Philippe; Nix, Wilfred; Liguori, Rocco; Schofield, Ian; Maderna, Luca; Czell, David; et al.
Abstract : Objectives: To study inter- and intra-rater agreement on diagnostic criteria for amyotrophic lateral sclerosis (ALS). Methods: Four-hundred-and-two patients referred for ALS were classified according to the revised El Escorial criteria (EEC) and the Awaji criteria (AwC) independently by eight experienced physicians from seven different countries. Intra-rater agreement was further assessed from 352 of the cases, which were interpreted twice by the same physician. Clinical and electrophysiological data were presented in standardised forms. Results: Two-by-two Kappa coefficients among the eight physicians varied from 0.15 to 0.75 (mean 0.40) for EEC and from 0.18 to 0.80 (mean 0.43) for AwC. Kappa coefficients for intra-rater agreement varied from 0.08 to 0.81 (mean 0.56) for EEC and from 0.18 to 0.85 (mean 0.67) for AwC. Disagreement was seen on all diagnostic categories, most pronounced for "probable lab-supported" and "possible". There were no differences between EEC and AwC. Discussion: The large variation on EEC and AwC may be due to the complexity of the criteria including the definition of four body regions, interpretation and significance of clinical findings of upper or lower motor neuron signs, significance of findings being rostral or caudal to each other, and interpretation of detailed electrophysiological findings as evidence of acute or chronic denervation. Conclusions: The large variation in interpretation of both EEC and AwC may be considered unacceptable for criteria used to include patients in research studies. Significance: Variability on interpretation of diagnostic criteria for ALS should be considered in the assessment of scientific studies. Initiatives to develop more reproducible diagnostic criteria for ALS are needed.